Lean Management and Sustainable Development at Universities: Needs and the Possibilities of Implementation Within the Context of Strategic Provisions - Detyna, Beata (Journal of Public Governance, 2023)
Objective: The aim of this article is to evaluate how university strategies align with sustainable development principles and integrate Lean Management for continuous improvement. The main research problem was finding the answer to the question: to what extent do the provisions (strategic goals) contained in the university’s strategies relate to the concept of sustainable development and fit into the main idea of Lean Management, i.e. continuous improvement? The paper presents the partial results of the research project aimed at proposing a model for implementing Lean Management (LM) at a university and a self-assessment form of the effectiveness and efficiency of the methods and tools used by the university (as part of LM).Research Design & Methods: The research methods used were a combination of qualitative content analysis, comparative analysis, and literature review to explore the integration of sustainable development and Lean Management concepts within university strategies. The data sources were strategic plans, sustainability reports, and other relevant documents from the Monash University, the Warsaw School of Economics (SGH), and other institutions.Findings: Modern strategies of universities very often refer to the need to constantly adapt their offer (research, teaching) to contemporary social and economic needs. By balancing the development of universities, strategies and planned activities fit into the concept of sustainable local, regional, national, and global development. Therefore, it is important to recognise universities’ current needs and possibilities regarding implementing sustainable development as part of research carried out in the academic environment and to search for effective and efficient methods and tools that will serve it.Implications/Recommendations: The research advocates for universities to adapt strategies to meet contemporary societal needs, emphasising sustainable development and Lean Management principles. Addressing wastefulness and promoting continuous improvement encourages the integration of Lean Management into university strategies, aligning with sustainability goals and enhancing organisational efficiency.Contribution/Value Added: The article recognises universities’ current needs and the possibilities for implementing sustainable development and searching for adequate methods and tools for these challenges.Article classification: research articleJEL classification: I2